2010
DOI: 10.1200/jco.2009.23.2272
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the International Adjuvant Lung Cancer Trial Evaluating Adjuvant Cisplatin-Based Chemotherapy in Resected Lung Cancer

Abstract: PURPOSE Based on 5-year or shorter-term follow-up data in recent randomized trials, adjuvant cisplatin-based chemotherapy is now generally recommended after complete surgical resection for patients with non-small-cell lung cancer (NSCLC). We evaluated the results of the International Adjuvant Lung Cancer Trial study with three additional years of follow-up. PATIENTS AND METHODS Patients with completely resected NSCLC were randomly assigned to three or four cycles of cisplatin-based chemotherapy or to observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
246
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(258 citation statements)
references
References 30 publications
5
246
1
6
Order By: Relevance
“…On the other hand, platinum-based chemotherapy is effective for patients with NSCLC in American and European countries. The IALT (International Adjuvant Lung Trial) shows that platinum-based chemotherapy for patients with NSCLC improves a 5-year survival rate by 4.1% (Arriagada et al, 2004), but there is no significant benefit after follow-up for 90 months (Arriagada et al, 2010). The CALGB 9633 trial results in a similar finding (Strauss et al, 2008).…”
Section: Introductionsupporting
confidence: 68%
“…On the other hand, platinum-based chemotherapy is effective for patients with NSCLC in American and European countries. The IALT (International Adjuvant Lung Trial) shows that platinum-based chemotherapy for patients with NSCLC improves a 5-year survival rate by 4.1% (Arriagada et al, 2004), but there is no significant benefit after follow-up for 90 months (Arriagada et al, 2010). The CALGB 9633 trial results in a similar finding (Strauss et al, 2008).…”
Section: Introductionsupporting
confidence: 68%
“…Conversely, in two other studies, the combination of cisplatin and the vinca alkaloid vinorelbine was used. (12,13) Unlike the study conducted by Arriagada et al, (11) those two other studies produced promising results: an improvement in survival was confirmed after a long follow-up period. In another study, (14) this improvement was 11% after more than nine years of follow-up, which is in disagreement with the findings of the Arriagada et al study.…”
contrasting
confidence: 52%
“…However, the results of a study conducted more recently by the same group of authors (11) revealed an increase in the mortality rate after a five-year median follow-up period. Therefore, the initial improvement in survival lost statistical power, with a benefit of 3.9% (p = 0.10).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Cisplatin based adjuvant chemotherapy can reduce the recurrence risk but there is no consensus in decision of adjuvant chemotherapy in lymph node negative early stage I and IIA NSCLC patients. IALT trial demonstrated the 4% survival advantage at 5 year but this has not been continued at 7 year follow-up in stage II and III NSCLC patients (Arriagada et al, 2010). JBR.10 trial reported survival advantage for resected NSCLC patients over 9 years of follow-up .…”
Section: Discussionmentioning
confidence: 99%